Monitoring of Marine Pollution - Bachari Fouzia, Houma (IntechOpen, 2019)
Many of the pollutants discharged into the sea are directly or indirectly the result of human activities. Some of these substances are biodegradable, while others are not. This study is devoted to monitoring areas of the environment. Methods assessment is based on monitoring data and an evaluation of the impact of pollution.Surveillance provides a scientific basis for standards development and application. The methodology of marine pollution control is governed by algorithms and models. A monitoring strategy should be put in place, coupled with an environmental assessment concept, through targeted research activities in areas identified at local and regional levels. This concept will make it possible to diagnose the state of "health" of these zones and consequently to correct any anomalies. Monitoring of the marine and coastal environment is based on recent methods and validated after experiments in the field of marine pollution.